Socio Economic and Cultural Life of Medieval India by Foreign Travelers: Exploring India through the Eyes of Foreign Travelers (Journal of Advances and Scholarly Researches in Allied Education, 2019)
A travelog or an itinerary is a travel writing of literary worth. It regularly records the encounters of a creator visiting a spot for the delight of travel. In post-old style times Muslims and Chinese commanded in travel writing however Europeans took the focal stage in travel and travel writing during the early present day time (From 1500-1800 A.D.). Europeans dared to the inaccessible comers of the globe and European print machines produced a large number of travel accounts that portrayed remote land and people groups. The volume of travel literature was extraordinary to the point that few editors, including Giambattista, Ramusio, Richard Hakluyt, Theodore de Bry and Samuel Purchas amassed various travel accounts and made them accessible in distributed assortments. Throughout the hundreds of years India has consistently been the object of remote intrigue which has driven scholars, conquerors missionaries, journalists and travelers to wander portrayals and arrangements. Remote endeavors at portraying the sub-landmass have extraordinarily affected individuals imaginaries, causing the introduction of a cliché vision of the nation which by one way or another has made due until today, both in the West where those records were created and in India itself.